2015
DOI: 10.22260/isarc2015/0103
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Construction Technology Implementation Framework: An Empirical Study

Abstract: Implementation of new technology is often required when a company wants to improve productivity and enhance safety in construction. Many studies in the literature have focused on new technology applications in the construction industry and how it can improve productivity or solve a complex problem. However, the literature has overlooked how a construction company introduces new technology and especially what attributes and other considerations (e.g. spare parts and down time) affect the adoption decision. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Rogers, et al [44] found that technical downtime contributed high probabilities to unsatisfied BIM implementation results. In this study, DT is measured in three aspects: the identification of DT as a risk (DT1), likelihood of DT occurrence (DT2), and consequence of DT occurrence (DT3)…”
Section: Ease Of Implementationmentioning
confidence: 99%
“…Rogers, et al [44] found that technical downtime contributed high probabilities to unsatisfied BIM implementation results. In this study, DT is measured in three aspects: the identification of DT as a risk (DT1), likelihood of DT occurrence (DT2), and consequence of DT occurrence (DT3)…”
Section: Ease Of Implementationmentioning
confidence: 99%
“…Ease of use is one of the main advantages of a new information technology [29]. The implementation attributes including ease of use of a new technology are critical measurements of technology adoption in construction [21,23,25]. The reason is that the construction industry is a naturally low-skilled labor based industry, and they are less likely to use complicated technologies.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In order to facilitate the uptake of these technologies, future studies should develop new applications for monitoring buildings. The technology adoption closely depends on the compatibility and interoperability of numerical analysis programs with building information modelling, usefulness of the new technologies, vendor support, and applicability of these technologies [30][31][32][33][34][35][36][37][38][39]. As mentioned, a building information model (BIM) of the Sydney Opera house was created based on as-built information for the management of on-going maintenance works on the site.…”
Section: Suggestions For Further Studiesmentioning
confidence: 99%